Legal Policy as a Tool to Control the Circulation of Illegal Drugs and Their Impact on Public Health - Djembor Sugeng Walujo; Indah Susilowati (Ipso Jure, 2025)
The circulation of illegal drugs in Indonesia continues to increase quantitatively and qualitatively, targeting not only urban areas but also rural areas and educational institutions. Law Number 35 of 2009 concerning Narcotics should be the main foundation in controlling narcotics trafficking, but its implementation has not been effective. This study uses a normative juridical method by analyzing laws and regulations and law enforcement practices in the field. It was found that weak coordination between institutions, overlapping authority, and lack of rehabilitation facilities were the main obstacles. The legal approach that is still dominant is repressive in nature, but it actually worsens the condition, because it emphasizes more punishment for users than rehabilitation as a health approach. In addition, public awareness of the dangers of illegal drugs is still low due to the lack of community-based education. This condition shows that the existing legal policy has not been able to answer the complexity of the narcotics problem as a public health crisis. Comprehensive reforms in policy design, strengthening institutional synergies, and a more humanistic and preventive approach are needed to protect public health in a sustainable manner. This study recommends the transformation of the narcotics law paradigm from a punitive approach to a recovery and education-oriented public health protection approach.